PENGARUH CSR, LEVERAGE, KEPEMILIKAN MANAJERIAL DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN (PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE DI BEI 2012-2017) - AYU SELVIANA, MARA; ISBANAH, YUYUN (Jurnal Ilmu Manajemen (JIM), 2019)
The purpose of this study was to determine the effect of CSR, leverage, managerial ownership, and liquidityon financial performance. This type of research uses quantitative research. The sampling technique usespurposive sampling. Data collection was carried out through publications from the property and real estatesector for the 2012-2017 period on the IDX. The statistical analysis used in this study uses SPSS. Analysis oftechnical data in terms of this study uses the classic assumption test, multiple linear regression analysis andhypothesis testing. The analysis shows that CSR does not have a negative influence on financial performance.Leverage does not have a positive effect on financial performance. Managerial ownership has a negativeinfluence on financial performance. Liquidity has a positive effect on financial performance. Keywords: CSR; financial performance; leverage; liquidity; managerial ownership.